2017
DOI: 10.17061/phrp2711702
|View full text |Cite
|
Sign up to set email alerts
|

A long-term, strategic approach to evidence generation and knowledge translation in NSW, Australia

Abstract: There is a growing body of literature about the barriers to, and enablers of, the use of research evidence in policy and practice. Research funders are in a unique position to influence activities aimed at promoting research use. During the past decade, NSW (New South Wales) Health has systematically built and invested in an integrated population and health services research portfolio made up of different types of investment and policy focuses. Each of these investments has an explicit focus on translation.Ens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
(6 reference statements)
1
8
0
Order By: Relevance
“…This finding is consistent with the large body of literature describing the widespread differences between the research and policy worlds [26, 27, 37, 54], whereby researchers most often attempt to ‘push’ their research to policy agencies rather than ascertaining when there may be a policy ‘pull’ for evidence and building at least some of their research agenda to align with this [55, 56]. One mechanism governments in New South Wales [57] and others internationally [5861] employ to help develop long-term collaborations with researchers and increase the production of policy-relevant research is government-funded research centres. While as yet there have been few evaluations of such initiatives, it seems a potentially promising method of facilitating productive, lasting partnerships.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This finding is consistent with the large body of literature describing the widespread differences between the research and policy worlds [26, 27, 37, 54], whereby researchers most often attempt to ‘push’ their research to policy agencies rather than ascertaining when there may be a policy ‘pull’ for evidence and building at least some of their research agenda to align with this [55, 56]. One mechanism governments in New South Wales [57] and others internationally [5861] employ to help develop long-term collaborations with researchers and increase the production of policy-relevant research is government-funded research centres. While as yet there have been few evaluations of such initiatives, it seems a potentially promising method of facilitating productive, lasting partnerships.…”
Section: Discussionsupporting
confidence: 82%
“…Participants suggested that trusting, long-term relationships were generally a precursor to co-production. These were seen to be facilitated by policy agencies having a stable workforce; frequent staff changes in policy agencies are frequently cited as a barrier to successful evidence generation partnerships in the literature [31, 42] and policy agency-funded research centres [43].…”
Section: Discussionmentioning
confidence: 99%
“…And if so, what ‘smart’ policy- or practice-relevant research might help society and decision-makers anticipate and avert foreseeable harms caused by disruptive urban mobility, and enable them to put in place early-warning systems to alert them of unforeseen consequences? Conversely, for policymakers and practitioners, are they willing to form long-term trusted research partnerships with transport and health researchers, and to require that evidence is used to inform policy ( Thackway et al, 2017 ; Giles-Corti et al, 2015 )? This section provides examples of potentially fruitful lines of enquiry for researchers and policymakers and practitioners to pursue.…”
Section: Could Smart Research Ensure That We Have mentioning
confidence: 99%
“…Building on this existing strength in prevention research, the NSW Ministry of Health's population health research portfolio comprises different policy focuses and types of investment. 4 One such investment is the Prevention Research Support Program (PRSP).…”
Section: Introductionmentioning
confidence: 99%